2022
DOI: 10.3390/horticulturae8100929
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of PPV and PNRSV Viruses from Three Peach Cultivars Using Thermotherapy In Vitro, Including Optimization of Microshoots’ Multiplication and Rooting Medium

Abstract: Peach cultivars (’Elberta’, ‘Red Top’, and ’Dixie Red’) were studied for their in vitro adoptability and performance in producing virus-free plantlets. The thermotherapy method with increasing temperatures (25 °C to 37 °C) was applied for the elimination of famous peach infecting plum pox viruses (PPVs) and prunus necrotic ringspot virus (PNRSV), and the DS-ELISA test and RT-PCR technique were performed to confirm the production of virus-free microshoots. The application of 30 mg L−1 of Fe-EDDHA treatment resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Abdullahi and Lawrence (2022) reported that 7 days of heat treatment at 37/32°C prior to meristem preparation was sufficient to eliminate apple chlorotic leaf spot virus (ACLSV) from Shiro plum, while Koubouris et al (2007) applied heat treatment for 20 days at 35-37 °C to eliminate PPV from the apricot cultivar 'Bebecou'. Hesari et al (2022) applied heat treatment at 37 °C for 4 weeks and this resulted in 100% PPV-free and Prunus necrotic ring spot virus (PNRSV)-free peach plants. A 45-day-long period at 37/35°C was suitable for eliminating PPV, PNRSV and prune dwarf virus (PDV) from apricot cultivars (Křižan and Ondrušiková 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Abdullahi and Lawrence (2022) reported that 7 days of heat treatment at 37/32°C prior to meristem preparation was sufficient to eliminate apple chlorotic leaf spot virus (ACLSV) from Shiro plum, while Koubouris et al (2007) applied heat treatment for 20 days at 35-37 °C to eliminate PPV from the apricot cultivar 'Bebecou'. Hesari et al (2022) applied heat treatment at 37 °C for 4 weeks and this resulted in 100% PPV-free and Prunus necrotic ring spot virus (PNRSV)-free peach plants. A 45-day-long period at 37/35°C was suitable for eliminating PPV, PNRSV and prune dwarf virus (PDV) from apricot cultivars (Křižan and Ondrušiková 2009).…”
Section: Discussionmentioning
confidence: 99%